2001
DOI: 10.1034/j.1600-0560.2001.028003127.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of human herpes virus 8 DNA in paraffin‐embedded biopsies of HIV‐associated and classical Kaposi’s sarcoma by PCR

Abstract: These data suggest that HHV8 viral load in Kaposi's sarcoma is relatively low and does not differ in HIV-positive and HIV-negative samples. The importance of viral load determination for prognosis or treatment monitoring remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…The great majority of non-Kaposi sarcoma vascular tumors previously studied have, however, been negative for HHV-8 by PCR. 16,[27][28][29][30][31][32][33] Given that the positive cases in the present study all showed levels above our preset high threshold level, we believe our results do indicate the true presence of HHV-8, rather than representing 'false positives'. Regrettably, we did not have access to frozen tissue from these positive cases, and thus were unable to perform Southern blot confirmation.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The great majority of non-Kaposi sarcoma vascular tumors previously studied have, however, been negative for HHV-8 by PCR. 16,[27][28][29][30][31][32][33] Given that the positive cases in the present study all showed levels above our preset high threshold level, we believe our results do indicate the true presence of HHV-8, rather than representing 'false positives'. Regrettably, we did not have access to frozen tissue from these positive cases, and thus were unable to perform Southern blot confirmation.…”
Section: Discussionmentioning
confidence: 63%
“…During latent infection, the virus exists in the nucleus as circular, episomal DNA that expresses a small number of viral genes. 15 Although no significant difference in HHV-8 viral loads has been observed in biopsies from HIV-positive vs HIVnegative individuals with Kaposi sarcoma, 16 HIVinfected individuals have a more aggressive course with frequent dissemination to skin and visceral organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in immunocompromised patients HHV-8 has been reported to be a major risk factor for the development of Kaposi's sarcoma. 32,33 The aim of this study was to prospectively investigate the short-term effect of infliximab administration on reactivation of JCV, EBV, HHV-6, -7, -8, and CMV in active CD to determine any risks of life-threatening virus-related events during long-term follow-up.…”
mentioning
confidence: 99%
“…45,46 HHV-8 can be detected by PCR in paraffin-embedded tissue, although the viral load seems to be low. 47,48 It is much easier to perform IHC using the commercially available monoclonal antibody against HHV-8 that is directed against the C-terminus of the latent nuclear antigen-1 (LNA-1) encoded by the ORF-73 gene. 49 The presence of HHV-8 in the nuclei of proliferating cells in KS lesions may be demonstrated in all its epidemiologic variants and from the earliest phases of the process.…”
Section: Human Herpesvirusmentioning
confidence: 99%